Single-drop microextraction followed by in-drop derivatization for the analysis of organic compounds by gas chromatography - Constantine Stalikas (Pakistan Journal of Analytical & Environmental Chemistry, 2007)
Microextraction has become a buzz word in the recent years in the scientific area of analytical chemistry. Over the last decade, newer miniaturised approaches to liquid extraction have emerged, resulting in solvent and sample savings and less time consuming analysis. Single-drop microextraction (SDME) has been developed as a viable and easy-to-use method based on the partitioning between sample matrix and organic droplet phase. However, there are numerous examples where analytical derivatizations are required to enhance sensitivity, selectivity, extraction efficiency and overall quality of the data. Improvements resulting from derivatization in instrumental methods are well known. The absence of data in chemical reaction accompanied by mass-transfer in liquid-liquid and gas-liquid microextraction, calls for a meticulous treatment of SDME in-drop derivatization for the purpose of analytical implementation. Leveraging the inherent characteristics of an organic microdrop as a tiny reactor, a threefold aim is set out in order: Ι. to develop a theoretical approximation to the in-drop derivatization SDME using phenolic compounds for liquid-liquid and two aldehydes for gas-liquid, as model compounds, II. to gauge the significance of mass-transfer and chemical reaction in an organic drop viewed as an analytical reactor and III. to underscore the importance of the a priori knowledge of the characteristics of such a system related to its analytical aspects.